Introducing the Study of Nordic Cooperation - Stie, Anne Elizabeth (2020)
To rediscover Nordic cooperation this article develops a ‘conceptual grammar’ that provides general theoretical ‘images’ of cooperation that are systematically applied. Being supplementary analytical constructs, moreover, these images capture great variety and differentiation in Nordic cooperation. Next, this article provides a review of two sets of literature that are of particular relevance to this thematic issue. The first is a broader literature on European integration. The second is studies of Nordic cooperation. The article closes with an overview of the contributions to this thematic issue.